Determinan Prevalensi Stunting di Nusa Tenggara Tahun 2023 - Singrapati, Lalu Riza; Astuti, Erni Tri (Seminar Nasional Official Statistics, 2024)
Indonesia is one of the countries still facing high prevalence rates of stunting. The Nusa Tenggara Archipelago significantly contributes to the high prevalence of stunting in Indonesia, with rates far above the national average. The factors causing the high prevalence of stunting in the Nusa Tenggara Archipelago need to be identified, considering the spatial aspects, as this region consists of many islands with diverse topographies and geographical characteristics. This study aims to identify the factors influencing the prevalence of stunting in the Nusa Tenggara Archipelago, taking into account the spatial aspects. The analysis method used is spatial regression analysis using the Spatial Error Model (SEM). The results of this study reveal that there is a spatial effect on the prevalence of stunting among children in the Nusa Tenggara Archipelago, indicated by a Global Moran’s I value of 0.420. The districts/cities with the highest stunting categories are mostly located in East Nusa Tenggara Province, with a rate of 50 percent, while in West Nusa Tenggara Province it is only 3.13 percent. Variables affecting stunting prevalence include the percentage of infants receiving early initiation of breastfeeding, the percentage of infants receiving exclusive breastfeeding, the percentage of children under five with a Child Health Book, average years of schooling for women, per capita expenditure, the percentage of households not using electricity, the prevalence of food insecurity, and the average fish consumption per capita per week. Based on the study results, government intervention is urgently needed to address the issue of stunting in the Nusa Tenggara Archipelago.